TELAAH PROSES SUKSESI KHILAFAH PADA MATERI SEJARAH PERKEMBANGAN ISLAM MASA KHULAFAURRASYIDIN KELAS X MADRASAH ALIYAH - Mohamad Aso Samsudin; Ukhtul Iffah (Fakultas Tarbiyah, Universitas Ibrahimy, 2021)
Learn history can help someone to determine several options that will be made, how to act, and also to know all of the factor failure as well as the success in the past. So that's why material of history must be explained comprehensively in order to the wisdom that have taken by it is historical episodes would be implemented for students. Material study in this discussion is succession process of khilafah on the material history of Islamic development class X at senior high school. It turns out found that no standard system or procedure in the Islamic government. Proven by processes selecting leaders of Islam society in the Khulafaurrasyidin periods, almost all of them implementing different systems. There are similar aspects on the Khulafaurrasyidin systems includes candidates inauguration assessed by criterias of seniority, pieties, most can be keep integrity and entity of Islam societies. Ijtihad space given in Islam to implement government structure based on the people's wishes. That matter occurs cause of no postulate found about state concept.